Losing the faith: public sector work and the erosion of career calling - Cohen, Laurie; Duberley, Joanne; Smith, Pete (SAGE Publications, 2018)
This article tells the story of Dave, a welfare rights advisor who worked his way up to be Assistant Director of Social Services in a Midlands local authority. Dave joined the public sector with a sense of calling and a belief that local government could create positive social change. Over the next 25 years, however, Dave’s calling was increasingly challenged as his job and the context in which he worked were transformed. This article focuses on the ways in which Dave navigated the system in an attempt to ‘keep the faith’, before eventually taking early retirement.